Study On Electrostatic Extrusion Method For Synthesizing Calcium Alginate Encapsulated Iron Oxide - Ken, Giap Low; Soh, Fong Lim (JASPE, 2014)
Electrostatic extrusion method is used to produce polymer beads by dripping polymer mixtures into hardening solution using syringing system with electrostatic charges. Through this method, iron oxide particles can be encapsulated into calcium alginate polymer beads. The changes in characteristics of the produced bead can be observed through changing the physical parameter values of applied voltage, height of electrodes, flow rate, and needle sizes of the system. From experimental study using Response Surface Methodology (RSM) modeling, the diameter of produced beads significantly decreases when applied voltage increases and needle size decreases. The optimum parameters from RSM is determined as 4kV applied voltage, 2cm of electrodes height and 0.4mm of needle diameter while flow rate does not contribute significant effect on the system. Furthermore, instrumental and analytical studies are carried out to characterize the produced bead based on the bead sizes, sphericity, surface area and surface morphology. Other than that, a mathematical model is developed from basic equations related to the system on production of calcium alginate encapsulated iron oxide. The model is then improvised and validated via experiment and it shows good agreement with the experiment result where error of the models is 0.4% for bead diameter and 2.5% for bead sphericity.